STUDY ON CHEMICAL QUALITY AND INHIBITORY EFFICACY OF TRIGONA BEE (Tetragonula clypearis) HONEY FROM BREEDERS IN EAST LOMBOK DISTRICT AGAINST Pseudomonas aeruginosa IN VITRO: Study On Chemical Quality And Inhibitory Efficacy Of Trigona Bee (Tetragonula Clypearis) Honey From Breeders In East Lombok District Against Pseudomonas Aeruginosa Using In Vitro Analysis - Solatul Hifzi Ulan Nasri; Sri Widyastuti; Mutia Devi Ariyana (Pro Food, 2023)
The chemical properties and antimicrobial activity of honey can be affected by geographic location. The aim of this study was to determine the chemical quality and inhibition activity of trigona honey bee (Tetragonulaclypearis) from Breeders in East Lombok District against Pseudomonas aeruginosa in vitro. This study was conducted using completely randomized design (CRD) with one factor, namely the location of the trigona beekeeping which consisted of 6 (six) locations, namely breeders Dames Damai, Bintang Rinjani, Sukarema, Bebidas, Banjar Sari and Geres.). Data were analyzed by analysis of variance (ANOVA) at a significance level of 5% using Co-Stat software. Significantly different data were tested with an Honestly Significant Difference (HSD). Data of phytochemical compounds (tanins and flavonoids) were analyzed using a descriptive method. The results showed that trigona honey had significantly different pH, water content, and reduced sugar content. The pH of trigona honey obtained from 6 farms in East Lombok Regency is in the general pH range of trigona honey, which ranges from 2.99 to 3.33. Meanwhile, the water content of trigona honey obtained from 6 farms in East Lombok Regency was very high, namely 27.98 - 41.01% (bb) with very low reducing sugar levels, which only ranged from 25.22 - 30.92%. However, the antimicrobial activity of trigona honey from 6 breeders in East Lombok showed the inhibition activity to Pseudomonas aeruginosa is relatively high that indicated by the formation of an inhibition zone due to the existence of flavonoid content in trigona honey as an antimicrobial agent.